DIGITALISASI FORMULIR PERMOHONAN PENYEWA ASET LAYANAN DINAS PERIKANAN BANYUWANGI BERBASIS WEB - Nur Sahila Chapsah; Zaehol Fatah; Fikri Rostina (CV. Denasya Smart Publisher, 2025)
The digitalization information system for asset application forms at the Banyuwangi Fisheries Service is a research to design and implement an information system that can support the processing of asset tenant data through a web-based platform. The purpose of this research is to overcome the problem of managing asset tenant data which is often complicated and time-consuming, and to provide better accessibility to users. This research uses data collection methods through literature reviews and interviews related to asset tenant data management. According to needs analysis. The information system is designed using web technologies such as HTML, CSS, JavaScript and PHP using the Laravell framework. The resulting information system includes crucial features such as applicant characteristics, usage plans, requested assets and rental periods. Users can practically access this website anywhere and anytime. The results of this study show that the website-based asset tenant application information system provides significant benefits for agencies and the community, including increasing efficiency in managing asset data, reducing errors in data processing and facilitating access to information from different devices.